Life Cycle Assessment and Sustainability in Eco-Concrete with Seashell Waste: A Systematic Literature Review - Brescia-Noranmbuena, L (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
This paper presents a systematic literature review of articles that include a life cycle assessment and sustainability assessment to measure the potential impacts of seashell waste usage in concrete production, the geographical context, and existing knowledge gaps. Concrete s extensive production has significant environmental impacts due to resource depletion and ecosystem threats. Sustainable alternatives, like seashell waste, are explored, with life cycle assessment and sustainability analysis aiding in evaluating their environmental performance and promoting circular economy principles. Following PRISMA guidelines, a comprehensive review of eco-concrete with seashell waste was conducted. Search strategies were refined to include related terms, and rigorous screening processes were employed for article selection and data extraction. A literature search yielded 66 articles on seashell waste in concrete, with 33 selected for review through initial and secondary screenings of studies. Studies primarily focused on seashells as an aggregate or cement substitute. Findings indicate that seashell waste as a construction material has been studied to a limited extent, with few studies utilizing life cycle assessment tools. However, some existing quantitative and qualitative sustainability analyses suggest seashell waste could be a promising and sustainable option for construction materials. Geographically, Spain leads in research, with China and Iran also prominent. Furthermore, we conducted a content analysis using Leximancer software to identify and evaluate concept maps through current research domains and emerging trends. Life cycle assessment, environment, and sustainability are common themes among the articles studied. This review also identifies limitations in bias, article heterogeneity, and search scope. Opportunities exist for a circular economy approach in cement production using seashell waste, but future research should explore its economic, environmental, and social impacts. Recommendations include expanding life cycle assessment studies, improving sustainability analyses, and using tools like the Integrated value model for sustainable evaluation.